Harmonisasi Pajak Tidak Langsung atas Konsumsi di Negara-Negara Anggota ASEAN - Gunadi, GUNADI; NURCHAMID, TAFSIR; SETYOWATI, MILLA SEPLIANA; JATI, WISAMODRO (UI Scholars Hub, 2011)
This research discusses the possibility of harmonizing indirect consumption tax system in the ASEAN member countries, inter alia, Indonesia, Vietnam, Malaysia and Singapore with three principal goals: (1) to explain the provision of indirect consumption tax system in that four countries, (2) to describes the process of indirect consumption tax system in the EU, and (3) to analyze the alternative of indirect consumption tax system in the ASEAN member countries. In order to encourage the operational of AFTA aiming at the free movement of goods and services within this region, indirect consumption tax becomes important phenomenon to talk about because despite her contribution to the state revenues, this kind of tax may conctitute an obstacle of this cross- border free movement of goods and services. To overcome this problem, with the reference of what has been done in the European Union, it appears that it is the appropriate time to discuss the harmonization of indirect consumption tax. However, it is no doubt that some problems may arise due to the differences in the applicable law of each country, including rates, and formal law as well. Furthermore, the different in administrative systems may also lead to difficulties in administering the tax and control over tax harmonized system. The introduction of a single standard rate and an acceptable ”uniform system” become issues to be much discussed, especially related to revenue, uniform model policy and implementation, including mechanism to minimize tax fraud.